2019
DOI: 10.1083/jcb.201810134
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive knockout analysis of the Rab family GTPases in epithelial cells

Abstract: Rab small GTPases (∼60 genes in mammals) are the master regulators of intracellular membrane trafficking. Homma et al. establish a comprehensive collection of knockout epithelial cell lines for all the mammalian Rabs, revealing that Rab6 is required for basement membrane formation and soluble cargo secretion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
85
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(94 citation statements)
references
References 62 publications
(88 reference statements)
8
85
1
Order By: Relevance
“…RAB6A has been implicated in matrix protein secretion, cell-matrix interactions and cell polarity in different models (Shafaq-Zadah et al, 2016;Fourrière et al, 2019;Homma et al, 2019). In contrast, our data indicate that loss of Rab6a in the luminal secretory lineage had no major impact on the structure of the mammary tissue.…”
Section: Loss Of Rab6a Affects Prlr Expression and Its Downstream Stacontrasting
confidence: 47%
See 3 more Smart Citations
“…RAB6A has been implicated in matrix protein secretion, cell-matrix interactions and cell polarity in different models (Shafaq-Zadah et al, 2016;Fourrière et al, 2019;Homma et al, 2019). In contrast, our data indicate that loss of Rab6a in the luminal secretory lineage had no major impact on the structure of the mammary tissue.…”
Section: Loss Of Rab6a Affects Prlr Expression and Its Downstream Stacontrasting
confidence: 47%
“…Potentially, other RAB proteins, highly expressed in the luminal secretory cells, could participate in maintaining apico-basal polarity features, in particular RAB8, a RAB GTPase implicated in the same post-Golgi transport pathways than RAB6A (Goud and Akhmanova, 2012). In addition, although expressed at very low level in the mammary tissue, RAB6B could have some compensatory function in the absence of RAB6A, as reported for RAB6-KO MDCK cells (Homma et al, 2019).…”
Section: Although Less Enriched In Integrins Than Basal Cells Luminamentioning
confidence: 55%
See 2 more Smart Citations
“…Only for the Rab1A and Rab1B, it was shown that at least one of them is required for cell viability [39]. In contrast, double knockout of Rab11A and Rab11B or Rab6A and Rab6B showed that neither pair is required for cell viability [40].…”
Section: Golgi Rabsmentioning
confidence: 99%